PENGARUH PENGGUNAAN MEDIA PUZZLE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI KALUKU BODOA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using puzzle learning media on the mathematics learning outcomes of fourth-grade students of Kaluku Bodoa Elementary School. This study uses a quantitative approach with a quasi-experimental design, namely a non-equivalent control group design. The research sample consisted of 62 students consisting of the experimental class and the control class. Data collection techniques used pretest and posttest tests. The results showed that the average value of the experimental class increased from 64.35 to 81.61, while the control class increased from 58.06 to 67.26. The results of the hypothesis test showed a significance value of 0.001 <0.05, meaning that H₀ was rejected and H₁ was accepted, so there was a significant effect of using puzzle media on students' mathematics learning outcomes. Thus, puzzle media can improve student activity, conceptual understanding, and learning outcomes.